Buoyancy effects on coupled heat transfer of supercritical pressure CO2 in horizontal semicircular channels. (May 2019) - Zhang, Haiyan; Guo, Jiangfeng; Huai, Xiulan; Cui, Xinying; Cheng, Keyong
Highlights: The best placement of the semicircular tube for horizontal flows is obtained. The heat transfer behavior has a lot to do with the flow characteristics near the wall. The entransy dissipation theory can explain the local heat transfer behavior very well. A new buoyancy criterion concerning vorticity is introduced for horizontal flows. Abstract: The buoyancy has great influence on the convective heat transfer of supercritical pressure fluids whose thermal properties change drastically near the pseudocritical point. Thus, numerical investigations on the coupled heat transfer characteristics of supercritical pressure CO2 (S-CO2 ) in horizontal semicircular channels are conducted in the present study. The effect of the secondary flow induced by buoyancy on the local thermal performance is analyzed in detail, and the dimensionless number Se, which represents the absolute vorticity flux in the main flow, is employed to describe the secondary flow and estimate the buoyancy effect. The numerical results show that the buoyancy effect gets smaller with the increase of the mass flow rate, and the heat transfer performance in the asymmetric flow is superior to that in symmetric flows at low mass flow rate. The buoyancy could significantly improve the thermal performance on the top wall but deteriorate that on the bottom wall in the hot side, which is exactly opposite in the cold side. The local wall heat transfer enhancement could be attributed to thinner thermal boundary layer due to the secondary flow, and the entransy dissipation theory could well explain the local heat transfer behavior. The criterion Se/Re gives better prediction for the buoyancy effect on both overall and local heat transfer than the existing ones.